Coach-Athlete Intimacy Towards Athlete Psychology: A Scoping Review - Indarto, Asyidika Vito; Prabowo, Trisnar Adi; Afifah, Mar'atul; Hamzah, A. Alfian Laitsilah; Antoro, Wisnu Pudi (Jurnal Pendidikan Jasmani (JPJ), 2025)
The purpose of this study was to map the scope of available evidence, identify key concepts, and existing research gaps related to the influence of coach-athlete intimacy on various dimensions of athlete psychology. This study used a scoping method, so that it could analyze and explore gaps in the existing literature. Literature searches included PubMed, Scopus, Web of Science (WOS), PsycINFO, SPORTDiscus, Garuda. The criteria for articles were in English and Indonesian between 2015 - 2025, discussing the relationship between coaches and athletes and its impact on athlete psychology, publications in peer-reviewed journals. So that 5 articles were found that were worthy of analysis. The results are that coach-athlete intimacy has been shown to reduce anxiety, increase motivation and self-confidence. In addition, coach-athlete intimacy can be a mediator between training performance and other psychological factors. So the quality of the coach-athlete relationship is an important foundation in the sports coaching process. Further research is expected to deepen other methodologies and analyses such as gender, age, type of sport, coach competence, in order to reveal more about athlete psychology from coach-athlete intimacy.